Radiation effects on electronic circuits in a spatial environment - Merabtine, N.; Benslama, M.; Benslama, A.; Sadaoui, Dj. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The failings bound to the deterioration of the components under irradiations are complex and numerous. This paper describes the different kinds of radiations present in the space as well as their interactions with the materials composing the integrated circuits used in the spacecraft. Our survey will be focused on the Single Event Upset phenomenon induced by the passage of only one ionizing particle with applications on the Samsung SDRAM.